Incidence and Risk Factors of Post-renal Transplantation Malignancies in North of Iran, A 20-year Experience (Iranian Journal of Kidney Diseases, 2020)
Introduction. The main causes of death in kidney transplant recipients are cardiovascular diseases and malignancy. This study aimed to determine the types of post-transplant malignancy, incidence, and related factors in renal transplant recipients referred to Razi Hospital in Rasht, Iran. Methods. This retrospective cross-sectional study was conducted on 549 kidney transplant recipients between 1998 and 2018. Patient-, transplant-, and medication-related factors and pathology reports were recorded in the check list. Chi-square, T-test and Logistic Regression were used to investigate the effect of variables. Malignancy-person-year incidence rate was calculated using survival tables and Kaplan-Mayer analysis. Results. 43 (7.8%) recipients had malignancies. The most common site of malignancy was the skin (53.5%). Non-Melanoma Skin Cancer (NMSC) was the most common cancer (32.6%) followed by Kaposi sarcoma (20.9%). The standardized incidence ratio (SIR) of post-transplant malignancies in renal transplant recipients was 26.9 times the malignancies in Guilan province and 21.7 times the malignancies in Iran. Cox proportional hazard models identified older age at the time of transplantation and history of azathioprine consumption seems to be associated with risk for post-transplant malignancy. Conclusion. The most common malignancies in these people were non-melanoma skin cancer, Kaposi sarcoma and then GI malignancies. According to the information obtained in this study, regular periodic examinations of kidney transplant recipients for early detection of malignancy is important.